1993
DOI: 10.1017/s0014479700021189
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Agronomic Effects on the Growth of Four Peanut Cultivars in a Sub-tropical Environment. I. Dry Matter Accumulation and Radiation Use Efficiency

Abstract: SummaryFour peanut cultivars of Spanish or Virginia botanical type and varying time to maturity were grown at a range of plant densities (44 000 to 352 000 plants ha-1) and spatial arrangements under irrigated conditions in sub-tropical southern Queensland, Australia. Total and pod dry matter production of the very early maturing Spanish cultivar Chico showed strong positive responses to increased plant density up to the highest density tested. Responses were less pronounced for the later maturing Spanish cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 28 publications
4
23
0
Order By: Relevance
“…Despite expectations of a kind of genetic dilution to phenotype variability among cultivars, genotype differences were quite strong for growth traits. Previously documented cultivar differences in leaf weight and harvest index do exist, but again these were in widely diverse botanical types (Bell et al, 1993a;Craufurd et al, 2002;Banterng et al, 2003), making the current study's documentation of growth variability among closely related cultivars unique. Although year had a significant effect on these traits indicating an effect of climate on peanut physiology, there were largely no interactions between year and genotype indicating that the changes caused by climate were relatively low in magnitude and did not alter the overall genetic pattern of development for each cultivar.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Despite expectations of a kind of genetic dilution to phenotype variability among cultivars, genotype differences were quite strong for growth traits. Previously documented cultivar differences in leaf weight and harvest index do exist, but again these were in widely diverse botanical types (Bell et al, 1993a;Craufurd et al, 2002;Banterng et al, 2003), making the current study's documentation of growth variability among closely related cultivars unique. Although year had a significant effect on these traits indicating an effect of climate on peanut physiology, there were largely no interactions between year and genotype indicating that the changes caused by climate were relatively low in magnitude and did not alter the overall genetic pattern of development for each cultivar.…”
Section: Discussionmentioning
confidence: 80%
“…There is true value in studies that examine growth and developmental differences among crop cultivars because they describe genetic variability that can either be utilized in breeding programs or crop models (Bell et al, 1991b;Bell et al, 1993a;Craufurd et al, 2002;Baterng et al, 2003;Kiniry et al, 2005). For breeding programs, a description of the differences among cultivars is essential for exploiting available genetic variability during the development of new germplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Alimadadi et al (2006) reported significant difference in RUE between different cultivars of red bean and vetch and found that with increasing leaf area index and decreasing LEC, RUE was increased between varieties of beans. Bell et al (1993) showed that with increasing LEC in peanuts from 0.3 to 1, the RUE was decreased from 2.75 to 1.5 g MJ -1…”
Section: Radiation Use Efficiencymentioning
confidence: 99%
“…Alimadadi et al (2006) found statistically significant difference for LEC and RUE among various cultivars of red beans and stated that with increasing leaf area index (LAI) and reduced LEC, RUE was increased in bean cultivars. Bell et al (1993) showed that with increase in LEC from 0.3 to 1, RUE was decreased from 2.75 to 1.5 g MJ -1 in peanut. Also such results have been reported in C 4 plants (Kiniry et al, 1989).…”
Section: Introductionmentioning
confidence: 96%
“…The RUE of chickpea can be affected by several factors such as planting date (Hughes et al 1987;Anwar et al 2003), plant growth habit (Hughes et al 1987), row spacing (Leach andBeech 1988), and irrigation (Leach and Beech 1988;Singh and Sri Rama 1989;Thomas and Fukai 1995;Anwar et al 2003). The estimated values of RUE can also depend on growing environment (Hughes et al 1987;Bell et al 1993;Kiniry et al 2001), disease pressure on the crop (Thomson and Siddique 1997), and growth resources such as available nutrients (Loomis and Amthor 1999). In our study, water deficit during the 2003 growing season was severe, resulting in decreased RUE; similar results were reported in a Mediterranean (Thomson and Siddique 1997) and a semiarid tropical environment (Singh and Sri Rama 1989).…”
Section: Radiation Use Efficiencymentioning
confidence: 99%